Sex, Gender and Time in Fiction and Culture
XI, 222 p.
Keywords: Investigating modern art, literature, theory and the law, this book illustrates the different ways in which sex, gender and time intersect. It demonstrates that time offers new critical perspectives on sex and gender and makes problematic reductive understandings of sexual identity as well as straight and queer time.